Computational Reproduction and Robustness Replication for Hollyer, Klašnja and Titiunik (2022): A Replication Report from the Nottingham Replication Games - Edmund Kelly; Angela Odermatt; Lennard Metson (Institute for Replication (I4R), 2023)
Hollyer, Klašnja, and Titiunik (2022) analyse the trade-off that political parties face between running programmatic campaigns and fielding charismatic candidates, whose electoral appeal may come at the cost of undermining the party brand. They argue that higher electoral volatility prompts parties to rely on charismatic candidates, even though they might not be as loyal to the party's programmatic stance. They substantiate their argument with a cross-national dataset and a quantitative case study in Brazil. We computationally reproduced and conducted further robustness tests for their cross-national study by translating the Stata code to R. Next, we conducted a computational reproduction and some additional robustness tests for the quantitative case study. We find that their cross-national analysis is reproducible, albeit with some minor discrepancies. The quantitative case study is also largely reproducible and both are robust in several ways. We conclude by making some suggestions about data dissemination and robustness checks for authors of regression discontinuity designs.
Keywords: 330